Characterization of coastal environment by means of hyper- and multispectral techniques. (February 2015) - Ciampalini, Andrea; Consoloni, Ilaria; Salvatici, Teresa; Di Traglia, Federico; Fidolini, Francesco; Sarti, Giovanni; Moretti, Sandro
Abstract: The management of the coastal environment is a complex issue, which needs for appropriate methodologies. Erosional processes and longshore currents present in the submerged beach represent a serious danger for both people and human infrastructures. A proper integration between traditional and innovative techniques can help in the characterization and management of the beach environment. Several different multispectral and hyperspectral techniques were used to retrieve information about the hydro and morphodynamic settings of the Pisa province coast (Tuscany, Italy). Results were validated using about 130 samples collected along the study area, between the mouths of the Serchio river and the Scolmatore canal. The composition of sand samples was evaluated by means of petrographic microscopy and grain size analyses. The same samples were analyzed using an Analytical Spectral Device (ASD) Fieldspec. The obtained sediment spectral library was used to evaluate the differences in mineralogical composition, which can be related to different source areas. Results coming from spectroscopy were compared to those obtained from the petrographic and grain size analysis. Furthermore a multispectral aerial image was used to evaluate sediment distribution along the submerged beach, to map the geomorphic features and to detect the presence of longshore and rip currents. This works suggests that optical remote sensing technique can be profitably used in order to reduce the need for expensive and time consuming conventional analysis. Highlights: Grain size and petrographic analysis performed on coastal sediments. Analysis of the spectral signature of sediments. Analysis of multispectral image through different algorithms. Integration of the obtained results for coast management.